Enhancing Self-Regulated Learning with ChatGPT: A Study in Science Education - Fanny Rahmatina Rahim; Ari Widodo; Achmad Samsudin; Tina Hayati Dahlan (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
In the dynamic digital era, artificial intelligence (AI) like ChatGPT presents revolutionary opportunities to advance classroom learning, particularly in science education. This research focuses on the utilization of ChatGPT to develop a learning model that supports the enhancement of students' Self-Regulated Learning (SRL) abilities. The study investigates four main aspects: (1) How can student-centered science learning improve SRL skills such as goal setting, self-management, and reflection? (2) How can the use of active and collaborative learning strategies in science increase students' motivation and SRL? (3) How can formative and summative assessments focused on developing SRL skills enhance science learning? (4) What are the researchers' experiences in using ChatGPT as a tool to develop and refine learning units, and their reflective research on its use as a teaching aid? An exploratory methodology was applied, utilizing ChatGPT to generate teaching materials tailored to classroom needs. Initial findings highlight ChatGPT's potential to support the development of SRL skills by providing quick access to structured and verified information. However, its use must be carefully managed to prevent over-reliance and ensure critical evaluation of sources. Educators are responsible for guiding students in the wise use of AI, fostering critical thinking, and promoting independent learning. Integrating ChatGPT into lesson design can enhance science education by creating engaging units, providing clear rubrics, and supporting formative assessment. This research underscores the positive potential of ChatGPT in fostering inclusive and adaptive science education, while also addressing the need for responsible technology management to ensure student development and well-being.